Analysis of HBsAg, Anti-HCV, Anti-HIV, VDRL, and TPHA test results in patients diagnosed with condyloma acuminata - Unal, Alkim (Annals of Medical Research, 2023)
Aim: Anogenital warts (AGWs) are among the most common sexually transmitted viral infections characterized by verrucae located in the anogenital region due to human papillomavirus. Although tests for other sexually transmitted diseases are recommended for patients diagnosed with AGWs, there is not sufficient information concerning the frequency of coinfections. This study aimed to determine the frequency of coinfection with hepatitis B, hepatitis C, human immunodeficiency virus (HIV) and syphilis in patients diagnosed with AGWs. Materials and Methods: For the 401 patients who presented to the Dermatology Clinic of XXX Hospital between 2014 and 2020 and were diagnosed with AGWs by a dermatologist, the hepatitis B surface antigen (HBsAg), anti-hepatitis C virus antibody (anti-HCV), anti-HIV, venereal disease research laboratory and treponema pallidum hemagglutination test results, and demographic characteristics were recorded. As controls, 350 patients who presented to the same hospital for a check-up and who did not have AGWs according to systemic examinations were evaluated, and the HBsAg, anti-HCV and anti-HIV results and demographic characteristics of these patients were also recorded for comparisons. Results: Hepatitis B was positive in 12 (3%) patients in the AGW group and seven (2%) patients in the control group. Hepatitis C was positive in two (0.5%) patients in the AGW group and negative in all the controls. While two (0.5%) patients in the AGW group were HIV-positive, all the controls were HIV-negative. Conclusion: The frequencies of hepatitis B, hepatitis C and HIV were found to be significantly higher in the AGW group than in the control group.